$\begin{array}{1 1}(a)\;a=\sqrt{g^2+f^2-c}\\(b)\;a=\sqrt{g^2-f^2+c}\\(c)\;a=\sqrt{g^2+f^2+c}\\(d)\;\text{None of these}\end{array}$

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

Equation of circle $=x^2+y^2+2gx+2fy+c=0$-------(1)

Now consider a circle having (h,k) as centre and radius a

Equation of this circle is $(x-h)^2+(y-k)^2=a^2$

(i.e) $k^2+y^2-2hx-2yk+h^2+k^2-a^2=0$--------(2)

Comparing (1) & (2)

$h=-g,k=-f,a=\sqrt{g^2+f^2-c}$

Hence radius a=$\sqrt{g^2+f^2-c}$

Hence (a) is the correct answer.

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...